MANAGEMENT OF PREGNANT WOMEN, IN LABOR AND POSTPARTUM WOMEN WITH CORONAVIRUS (COVID-19) INFECTION - Dr. Amal Abdul Mahdi Kadhim; Hameda Ahmed Hamdan; Rasha Abduladheem Abbas Nassar (Scholar Express Journals, 2022)
Sixty-two patients were collected from different Hospitals in Iraq, where the research highlights management of pregnant women in labor and postpartum women with coronavirus infection (COVID-19). Where the demographic information of the patients was collected, where xray methods and diagnostic methods (simple radiography and computerized tomography of the chest organs) were used. Mean value and slandered division to the age of the patients were found, and it was 34.816 ± 2.57 With 14 patient, that is, form of 23.3%, and the following conclusion has been reached so far, there is no scientific evidence of an increased vulnerability of pregnant women to complications related to COVID-19 infection, and One of the most important characteristics of this virus is its rapid global spread, and in most cases, it results in a mild respiratory infection, and In addition, no significant differences were found with other perinatal outcomes in neonates For COVID-19 neonates, 50% of cases are asymptomatic
Keywords: Pregnant; COVID-19; asymptomatic; MERS